2010
DOI: 10.1097/fjc.0b013e3181ed064f
|View full text |Cite
|
Sign up to set email alerts
|

Congestive Heart Failure: Where Homeostasis Begets Dyshomeostasis

Abstract: Despite today's standard of care, aimed at containing homeostatic neurohormonal activation, 1 in every 5 patients recently hospitalized with congestive heart failure (CHF) will be readmitted within 30 days of discharge because of a recurrence of their symptoms and signs. In light of recent pathophysiologic insights, it is now propitious to revisit CHF with a view toward complementary and evolving management strategies. CHF is a progressive systemic illness. Its features include: oxidative stress in diverse tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 146 publications
1
20
0
2
Order By: Relevance
“…The recovery of hypercalciuria and hyperparathyroidism after treatment of PA patients further supports our interpretation. Kamalov and colleagues (19) suggested that hypercalciuria of aldosteronism was related to an expanded extravascular fluid volume resulting in decreased proximal tubular resorption of Na þ and Ca þþ , with consequent increase of their distal delivery. Because aldosterone promotes distal resorption of Na þ but not of Ca þþ , the net effect would be an increase in renal Ca þþ excretion.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of hypercalciuria and hyperparathyroidism after treatment of PA patients further supports our interpretation. Kamalov and colleagues (19) suggested that hypercalciuria of aldosteronism was related to an expanded extravascular fluid volume resulting in decreased proximal tubular resorption of Na þ and Ca þþ , with consequent increase of their distal delivery. Because aldosterone promotes distal resorption of Na þ but not of Ca þþ , the net effect would be an increase in renal Ca þþ excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated PTH maintains the level of extracellular ionized calcium, resulting in intracellular calcium overload, which is considered a calcium paradox. Intracellular calcium overload leads to myocardial remodeling and reactive oxygen and nitrogen free radicals, overwhelming the antioxidant defense system of the body and promoting the release of inflammatory cytokines such as interleukin-6 and tumor necrosis factor alpha (Grey et al, 1996;Kamalov, Bhattacharya, & Weber, 2010). In this sense, secondary hyperparathyroidism is a systemic illness (Alsafwah et al, 2007;Altay & Colkesen, 2013) responsible for osteopenia and osteoporosis as well as apoptosis of the myocardium and skeletal muscle, which affect various tissues.…”
Section: Discussionmentioning
confidence: 98%
“…Son dönem kalp yetmezliği (SDKY) olgularında, bozulan böbrek fonksiyonlarına ikincil vitamin D eksikliği, hipokalsemi ve bunlara bağlı gelişen sekonder hiperparatiroidizm, kemikteki osteoklastik aktivitede artış ve osteoblastik aktivitede azalma ile sonuçlanmaktadır (1,2). Ayrıca SDKY'ye bağlı gelişen böbrek fonksiyon bozukluğu ve glomerüler filtrasyon hızı (GFH) düşüklüğü ile uzun süreli lup diüretiklerinin kullanımına bağlı böbreklerden kalsiyum reabsorbsiyonu engellenmekte ve hipokalsemi derinleştirebilmektedir.…”
Section: Introductionunclassified